Differential Effects of Continuous Versus Discontinuous Aerobic Training on Blood Pressure and Hemodynamics. Issue 1 (January 2018) - Landram, Michael J.; Utter, Alan C.; Baldari, Carlo; Guidetti, Laura; McAnulty, Steven R.; Collier, Scott R.
Abstract : Abstract: Landram, MJ, Utter, AC, Baldari, C, Guidetti, L, McAnulty, SR, and Collier, SR. Differential effects of continuous versus discontinuous aerobic training on blood pressure and hemodynamics. J Strength Cond Res 32(1): 97–104, 2018—The purpose of this study was to compare the hemodynamic, arterial stiffness, and blood flow changes after 4 weeks of either continuous or discontinuous aerobic exercise in adults. Forty-seven subjects between the ages of 18 and 57 were recruited for 1 month of either continuous aerobic treadmill work for 30 minutes at 70% max heart rate or 3 bouts of 10 minutes of exercise at 70% of max heart rate with two 10 minutes break periods in between, totaling 30 minutes of aerobic work. After exercise, both continuous (CON) and discontinuous (DIS) groups demonstrated a significant improvement in maximal oxygen uptake (V[Combining Dot Above]O2 max, CON 35.39 ± 1.99 to 38.19 ± 2.03; DIS 36.18 ± 1.82 to 39.33 ± 1.75), heart rate maximum (CON 183.5 ± 3.11 to 187.17 ± 3.06; DIS 179.06 ± 2.75 to 182 ± 2.61), decreases in systolic blood pressure (CON 119 ± 1.82 to 115.11 ± 1.50; DIS 117.44 ± 1.90 to 112.67 ± 1.66), diastolic blood pressure (CON 72.56 ± 1.65 to 70.56 ± 1.06; DIS 71.56 ± 1.59 to 69.56 ± 1.43), augmentation index (CON 17.17 ± 2.17 to 14.9 ± 1.92; DIS 19.71 ± 2.66 to 13.91 ± 2.46), central pulse wave velocity (CON 8.29 ± 0.32 to 6.92 ± 0.21; DIS 7.85 ± 0.30 to 6.83 ± 0.29), peripheral pulse wave velocity (CON 9.49 ± 0.35 to 7.72 ± 0.38; DIS 9.11 ± 0.37 to 7.58 ± 0.47), and significant increases in average forearm blood flow (CON 4.06 ± 0.12 to 4.34 ± 0.136; DIS 4.26 ± 0.18 to 4.53 ± 0.15), peak forearm blood flow (FBF) after reactive hyperemia (CON 28.45 ± 0.094 to 29.96 ± 0.45; DIS 29.29 ± 0.46 to 30.6 ± 0.38), area under the curve (AUC) of FBF (CON 28.65 ± 1.77 to 30.4 ± 1.08; DIS 30.52 ± 1.9 to 31.67 ± 1.44), and AUC peak FBF after reactive hyperemia (CON 222.3 ± 5.68 to 231.95 ± 4.42; DIS 230.81 ± 6.91 to 237.19 ± 5.39). These data suggest that for healthy people either 4 weeks of continuous or discontinuous aerobic training is effective in improving measures of fitness and vascular health.